Cystic fibrosis: physical exercise versus chest physiotherapy - Ali Alfetory, Nesreen (faculty of Basic Medical Science - Libyan International Medical University, 2020)
Cystic fibrosis (CF) may be a life threatening disease resulting in accumulation of thick mucus which will affect the lungs , sudoriferous glands (sweet gland) and other organs , due to chromosomal mutation in CFTR gene that encodes the CFTR protein (cystic fibrosis trans membrane conductance regulator protein) this report is based on a study that has been done on 12 children with CF that include work out program , were the physiotherapy and aerosol inhalation was stopped for a span of 17 days of the program , but it didn't achieve to a major response.
Cystic fibrosis a genetic abnormality which will effect lungs , reproductive tract , and gastrointestinal system .It's an autosomal recessive disease , a chromosomal mutation in CF- associated gene that provide instruction to form CFTR protein (cystic fibrosis trans membrane conductance regulator protein) , this protein pumps chloride ions into different secretions this ion help draw water into the secretions which will wind up thinning that out .The abnormalities in this protein leads to an accumulation of thick , sticky , dehydrated mucus which will eventually clog the lungs and impair the mucociliary clearance and also gives an appropriate environment for bacterial growth